A critical review on the sources and instruments of marine microplastics and prospects on the relevant management in China - Wang, J.; Zheng, L.; Li, J.
The world's oceans are suffering a constant and unprecedented accumulation of emerging plastic contaminants known as microplastics with a particle diameter smaller than 5mm. Microplastics exhibit a widespread distribution in various habitats from land to the oceans, and even reach the most remote regions - the deep sea and the polar, receiving attention exponentially in the past few years. Owing to their small size, marine species risk getting ingested and entangled in microplastics, causing suffocation, starvation, physical trauma or damage from chemicals, which poses vast and growing threats to biodiversity and the food web. This review article focuses on the various sources attributed to marine microplastics, the latest international, regional and national countermeasures to combat marine litter, as well as the status quo of microplastics pollution, legislation and regulations in China, and furthermore provides improving proposals/solutions on key research gaps, governance and management for future environmental control and policymaking in China.
Keywords: INSTRUMENTS; MARINE ENVIRONMENT; MICROPLASTICS; PROPOSALS/SOLUTIONS; SOURCES